Allergic reaction to patent blue dye in breast surgery - case report - Maranhão,Marcius Vinícius M. (2016)
Abstract We present a case of allergic reaction to patent blue in a patient who underwent excision of sentinel lymph node associated with segmental breast resection. About 20 min after the dye injection, the patient developed hypotension (BP = 70 × 30 mmHg) associated with increased heart frequency. The patient was treated successfully with decreased inspired fraction of inhaled anesthetic and fluid replacement. At the end of the procedure, she presented with bluish urticarial-like plaques on the head, neck, upper limbs, and trunk; hydrocortisone was then used. The patient recovered uneventfully and was discharged from the PACU 2 h after the end of surgery without skin changes, and was discharged from hospital on the morning after surgery. The incidence of allergic reactions with the use of patent blue is far superior to the hypersensitivity reactions seen with anesthetic and adjuvant drugs. Therefore, the anesthesiologist must be aware of cardiovascular instability associated with skin changes during the use of patent blue, for early diagnosis and appropriate treatment of this hypersensitivity reaction to this dye.